SYSTEMATIC REVIEW AND META-ANALYSIS OF CHILDHOOD NUTRITION AND OBESITY IN PAKISTAN (Journal of Medical & Health Sciences Review, 2026)
The metabolic risks related to obesity are more in South Asian populations as compare to white or other ethnic groups. Similarly, levels of obesity in childhood of South Asians are known to track into adulthood. Childhood obesity is becoming an equally challenging in developing countries including Pakistan. Children and teenagers are effecting badly with an estimated 10% of the world's children being overweight and one quarter of these being obese. The purpose of this study is to assess occurrence and socioeconomic correlates of overweight and obesity, and trend in prevalence statistics, among Pakistani childhood. A Systematic Review and Meta-Analysis of Childhood Nutrition and Obesity analysis is carried out to estimate the results. In conclusion, addressing childhood obesity and nutrition issues in Pakistan requires a comprehensive approach involving education, policy changes, community engagement, and healthcare interventions. By implementing these strategies, we can work towards a healthier future for Pakistani children, reducing obesity rates and improving overall nutrition outcomes.